CLIMITE-RESPONSIVE ARCHITECTURE: DESIGNING FOR CHANGING WORLD (Modern education and development, 2025)
As climate change continues to impact weather patterns, ecosystems, and urban living conditions, architecture must evolve to meet these new challenges. Climate-responsive architecture refers to design strategies that adapt buildings to their local environmental conditions, reducing energy consumption while improving comfort and sustainability. This article explores the principles of climate-responsive architecture, innovative materials and technologies, and its critical role in shaping resilient, eco-friendly structures for the future.